Anticancer and chemopreventive potential of Morinda citrifolia L. bioactive compounds: A comprehensive update - Kitic, Dusanka; Miladinovic, Bojana; Randjelovic, Milica; Szopa, Agnieszka; Seidel, Veronique; Prasher, Parteek; Sharifi-Rad, Javad (Wiley, 2024)
Morinda citrifolia L., commonly known as Noni, has a longstanding history in traditional medicine for treating various diseases. Recently, there has been an increased focus on exploring Noni extracts and phytoconstituents, particularly for their effectiveness against cancers such as lung, esophageal, liver, and breast cancer, and their potential in cancer chemoprevention. This study aims to provide a comprehensive review of in vitro and in vivo studies assessing Noni's impact on cancer, alongside an exploration of its bioactive compounds. A systematic review was conducted, encompassing a wide range of scientific databases to gather pertinent literature. This review focused on in vitro and in vivo studies, as well as clinical trials that explore the effects of Noni fruit and its phytoconstituents-including anthraquinones, flavonoids, sugar derivatives, and neolignans-on cancer. The search was meticulously structured around specific keywords and criteria to ensure a thorough analysis. The compiled studies highlight Noni's multifaceted role in cancer therapy, showcasing its various bioactive components and their modes of action. This includes mechanisms such as apoptosis induction, cell cycle arrest, antiangiogenesis, and immune system modulation, demonstrating significant anticancer and chemopreventive potential. The findings reinforce Noni's potential as a safe and effective option in cancer prevention and treatment. This review underscores the need for further research into Noni's anticancer properties, with the hope of stimulating additional studies and clinical trials to validate and expand upon these promising findings.
Keywords: anticancer mechanisms; antitumor activity; chemopreventive; chemotherapeutic; Morinda citrifolia; Noni plant; Tahitian Noni fruit juice